Onlineeinkauf von Pflanzenschutzmitteln: Ein Discrete-Choice-Experiment mit landwirtschaftlichen Unternehmern in Deutschland; Online Purchases of Plant Protection Products: A Discrete Choice Experiment with Agricultural Entrepreneurs in Germany - Michael Danne; Wilm Fecke; Oliver Mußhoff (German Journal of Agricultural Economics (GJAE), 2021)
– Digitalization is progressing more and more and increasingly influencing business processes in companies. In this context, e-commerce plays an important role for the future development of rural areas. Nonetheless, there is so far no study which investigates the use of e-commerce for business purposes in rural areas. Hence, primary data was collected from 250 farmers by conducting a discrete choice experiment about the purchase of crop protection products. The "willingness to accept" (WTA) of agricultural entrepreneurs for e-commerce was estimated using a mixed logit model. The results show that agricultural entrepreneurs demand a discount when they purchase inputs via online trading rather than from their current trader. Furthermore, the presence of a private respectively state label for an online retailer has a positive effect on e-commerce usage. However, the longer delivery time has a negative effect on the use of e-commerce for crop protection product purchases. The results show that consultation and personal contact between the dealer and the customer are of great importance. These core findings are very relevant to business practice, as they provide online agricultural traders of agricultural inputs with initial clues regarding appropriate marketing measures and allow de-riving recommendations for policy measures. In addition, by considering individual-specific characteristics, it could be shown that there is a statistically significant relationship between the risk attitude and education level with the e-commerce acceptance of an agricultural entrepreneur.
Keywords: 330; E-Commerce; ländlicher Raum; Onlinehandel; Internetnutzung; Digitalisierung; landwirtschaftliche Unternehmer